2010
DOI: 10.3168/jds.2009-2295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on energetic metabolism in lactating Holstein cows

Abstract: Heat stress has an enormous economic impact on the global dairy industry, but the mechanisms by which hyperthermia negatively affect systemic physiology and milk synthesis are not clear. Study objectives were to evaluate production parameters and metabolic variables in lactating dairy cows during short-term heat stress or pair-fed conditions coupled with bST administration. Twenty-two multiparous Holstein cows were subjected to 3 experimental periods: 1) thermoneutral conditions with ad libitum intake for 7 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

87
622
16
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 660 publications
(749 citation statements)
references
References 43 publications
87
622
16
24
Order By: Relevance
“…Despite marked reductions in nutrient intake, heat-stressed cattle exhibit increased basal insulin levels and stimulated insulin response (Itoh et al, 1998; Bernabucci, Lacetera, Baumgard, Rhoads, Ronchi and Nardone 1172 Baumgard and Rhoads, 2007;Wheelock et al, 2010), and this agrees with heat-stressed rodent experiments (Torlinska et al, 1987). The increased basal and stimulated insulin levels may explain the lack of an increase in basal NEFA levels in heatstressed cows as insulin is a potent antilipolytic hormone (Vernon, 1992).…”
Section: Heat Stress In Ruminants 1171supporting
confidence: 59%
“…Despite marked reductions in nutrient intake, heat-stressed cattle exhibit increased basal insulin levels and stimulated insulin response (Itoh et al, 1998; Bernabucci, Lacetera, Baumgard, Rhoads, Ronchi and Nardone 1172 Baumgard and Rhoads, 2007;Wheelock et al, 2010), and this agrees with heat-stressed rodent experiments (Torlinska et al, 1987). The increased basal and stimulated insulin levels may explain the lack of an increase in basal NEFA levels in heatstressed cows as insulin is a potent antilipolytic hormone (Vernon, 1992).…”
Section: Heat Stress In Ruminants 1171supporting
confidence: 59%
“…Some authors demonstrated that IGF-I had a slight decrease during heat stress (Sarko et al 1994;Rhoads et al 2009;Wheelock et al 2010). In the present study, however, IGF-I concentrations were not influenced by ACTH administration or increase in plasma CORT concentration.…”
Section: Acth Administrationcontrasting
confidence: 48%
“…In the same way, while some authors have reported that growth hormone (GH) and insulin-like growth factor I (IGF-I) are negatively influenced by heat stress (Sarko et al 1994;Rhoads et al 2010;Wheelock et al 2010), others mentioned that IGF-I levels during heat stress are similar to those obtained within thermal comfort zone (McGuire et al 1991;Hirayama et al 2004;Chaiyabutr et al 2008;Collier et al 2008). For these reasons, the interactions between heat stress and CORT and between IGF-I and environmental heat remain controversial.…”
Section: Introductionmentioning
confidence: 92%
“…Similar to milk yield, fat content was highest at moderate WSs. Most previous studies also report a decrease in the proportion of fat in milk (Bouraoui et al, 2002;Hammami et al, 2013;Smith et al, 2013) or total milk fat (Lambertz et al, 2014) under conditions of heat stress or increasing temperature, although others found no effect (Knapp and Grummer, 1991;Wheelock et al, 2010). While an increase in the number of sunshine hours was associated with an increase in milk yield in cows outdoors and a decrease in milk yield in cows indoors, the inverse was true for fat content.…”
Section: Discussionmentioning
confidence: 93%